Pelaksanaan Asesmen Diagnostik Non Kognitif dalam Kurikulum Merdeka di MIN 2 Kota Sawahlunto - Elizasri; Ilyas, Asnelly (PT PUSTAKA CENDEKIA GROUP, 2023)
This research was conducted at Madrasah Ibtidaiyah Negeri 2, Sawahlunto City. This study aims to see and find out how the implementation of the diagnostic test in the Merdeka Curriculum in elementary schools. How was the preparation, implementation, and results. The implementation of the diagnostic assessment is very important to be carried out by the teacher at the beginning of the meeting. In this study, non-cognitive diagnostic assessment. Diagnostic assessment is a very important initial diagnosis in the implementation of the independent curriculum. With the aim to determine the basic abilities of each learner. from the results of the diagnostic assessment, the teacher can create suitable learning activities according to the needs of students. However, in reality the implementation of this new diagnostic assessment has created confusion for teachers at the State Elementary School 2, Sawahlunto City. Both in terms of preparation, implementation and results. Before being able to provide assistance appropriately, the teacher must first give a diagnostic test carefully and thoroughly. This study uses a qualitative descriptive approach, which will describe how the diagnostic test is carried out in the independent curriculum at Madrasah Ibtidaiyah Negeri 2 Sawahlunto City.